Water-filled heat pipes for CubeSat thermal control - Gerner, H.J. van; Brouwer, H.; Groot, Z. de; Guo, J. (IOP Publishing, 2018)
Currently, the amount of electrical power that is available for CubeSat's is very small and for this reason, simple thermal conductance through the frame of the CubeSat is sufficient for most CubeSat missions. However, deployable solar panels have been developed recently and peak powers up to 40W can now be generated. This higher generated electrical power results in more waste heat and potentially too high temperatures inside the CubeSat. For this reason, the use of water-filled heat pipes is studied, since these are cheap, widely commercially available, and can be bent in the desired shape. Both the condenser and evaporator thermal resistance and the total heat transfer capacity of these heat pipes have been measured for a wide range of temperatures with a unique automated setup that uses Peltier elements to control the temperature. Furthermore, the heat pipes have been subjected to multiple freeze/thaw cycles and start-ups from a frozen state. After these successful tests, a heat pipe was integrated in a CubeSat and tests were carried out in several orientations. The tests show that commercially available water-filled heat pipes are suitable for CubeSat thermal control.